International Control of investment : the Düsseldorf Conference on Multinational Corporations - Wallace, Don; Georgetown University (New York : Praeger Publishers, 1974)
This book was a proceedings of the Dtisseldorif Conference of 1973 which discussed exchange rates and other international monetary problems; international trade negotiation, the multinational corporation, and private foreign investment.
"Published in cooperation with the Institute for International and Foreign Trade Law, Georgetown University Law Center."
Includes bibliographic footnotes and index
usc 25/05/18
Loans
Keywords: Investments, Foreign; International business enterprises